EGFR Mutation in Patients with NSCLC and Its Relationship Between Survival and Clinicopathological Features: An Update Analysis - Ozturk, A.; Celik, S.; Kodaz, H.; Yildiz, I.; Ocak, A.; Hacibekiroglu, I.; Gumus, M. (Elsevier Science Inc, 2018)
[Abstract Not Available]
Keywords: EGFR mutation; NSCLC; treatment